Multidisciplinary Education: Strategies for Implementation - Walia , Parminder (Gyan Management Journal, 2023)
Multiple skills are required to be exhibited by an individual at the  workplace in order to be successful and productive. Skills like, critical  thinking, problem solving, team building, communication and ICT  are all required to perform any job effectively. Further, the solutions to  the problems in the real world do not lie in any one specific discipline,  rather need a multidisciplinary approach. Taking note of this issue,  The National Education Policy announced in 2020, has proposed a  shift towards multi-disciplinary education. The present paper dis cusses the various recommendations given by NEP 2020 with regard  to multidisciplinary education and the strategies that are needed to  implement these recommendations.
Keywords: National Education Policy 2020; Multidisciplinary Education